Case Report: Synergistic effects of an ASXL3 mutation and a 15q11.2 BP1-BP2 microdeletion in a severe neurodevelopmental phenotype - Yang, Mingkai; Xiao, Yanfang; Chen, Chanjuan; Chu, Zhou; Hu, Guohong (Frontiers in Genetics, 2025)
BackgroundBainbridge–Ropers syndrome (BRPS, OMIM #615485) and the 15q11.2 BP1-BP2 microdeletion syndrome (OMIM #615656) are distinct genetic aetiologies of neurodevelopmental disorder Dual diagnosis of both entities in a single patient is extremely rare, and the underlying synergistic pathogenesis remains poorly understood.MethodsWe report a 7-month-old boy presenting with severe global developmental delay, hypotonia, feeding difficulties, microcephaly and recurrent respiratory infections. Whole-exome sequencing (WES) was performed and a protein–protein-interaction (PPI) network was constructed using the STRING database to aid molecular diagnosis. Clinical management and 7-month outcome are described.ResultsWES identified a de novo nonsense mutation in ASXL3 (c.1094C>G, p. Ser365*) and a 1.22-Mb 15q11.2 microdeletion (BP1-BP2) inherited from the asymptomatic father, establishing a dual diagnosis. The PPI network revealed no direct or high-confidence (>0.4) interactions between ASXL3 and the 15q11.2 BP1-BP2 microdeletion-encoded proteins CYFIP1, NIPA1, NIPA2 or TUBGCP5, indicating convergence at the pathway rather than the complex level.ConclusionThe 15q11.2 BP1-BP2 microdeletion acts as a genetic modifier that may amplify the phenotypic expression caused by the core mutation in the ASXL3 gene. Haploinsufficiency of CYFIP1, NIPA1, NIPA2, and TUBGCP5 increases neurodevelopmental susceptibility, while the de novo truncating mutation in ASXL3 drives severe epigenetic dysregulation. Together, they precipitate the profound phenotype observed here. This case suggests that multilocus pathogenic variation can generate a blended, severe phenotype and underscores the need to consider polygenic burden plus gene–environment interactions in complex NDD. We proposed a “core mutation - gene regulator - environment” synergy hypothesis model, which is of significant guidance value for genetic counseling and personalized clinical management.